Study of the manifestations of visual pollution in some neighborhoods of Jeddah city: Comparative study - Bawareth, Reem Mohammed (Journal of Humanities & Social Sciences, 2022)
This research aims to identify visual pollution, its most important manifestations and types, the reasons that led to its emergence, and its impact on the psychological and physical health of humans. The descriptive and analytical approach is applied in the study of manifestations of visual pollution in some neighborhoods of Jeddah, comparing them and identifying the most polluted among them. The neighborhoods were selected according to the local schematic of Jeddah city- regulations and controls 1440H in the zoning of residential areas-. The study was in line with 2030's vision of improving the urban landscape in Saudi cities, one of its objectives to address visual distortions in Saudi cities. This research has found that the neighborhoods have different manifestations of visual pollution. Al-Hendaweyyah neighborhood is a slum area, were all manifestations of the urban style visual pollution appeared. In addition, graffiti on the walls clearly appeared. On the other hand, AL-Mohammadya is low-density residential area. It is a planned neighborhood, where the manifestations of visual pollution did not appear in compare with other one, with limited exception of graffiti. Finally, the study recommends developing a strategy to improve the visual landscape in slums by renovation of old buildings, Also, by developing terms and conditions for building exterior colors and packaging materials that suit the urban style of the area.
Keywords: visual pollution; Jeddah city; Saudi Arabia; mental and physical health